2020
DOI: 10.1002/adfm.202002625
|View full text |Cite
|
Sign up to set email alerts
|

Molecule Charge Transfer Doping for p‐Channel Solution‐Processed Copper Oxide Transistors

Abstract: The doping of semiconductors plays a critical role in improving the performance of modern electronic devices by precisely controlling the charge carrier density. However, the absence of a stable doping method for p‐type oxide semiconductors has severely restricted the development of metal oxide‐based transparent p–n junctions and complementary circuits. Here, an efficient and stable doping process for p‐type oxide semiconductors by using molecule charge transfer doping with tetrafluoro‐tetracyanoquinodimethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…Another problem is that it is difficult to p‐dope the TS/C because of defect compensation. [ 12 , 13 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another problem is that it is difficult to p‐dope the TS/C because of defect compensation. [ 12 , 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…As for the p‐type semiconductors, only Cu 2 O, SnO, NiO, and Rh 2 O 3 were demonstrated as potential candidates, but they suffered from insufficient hole transport with low mobility and inadequate optical transparency. [ 9 , 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to form nano-/micro-structured thin-films from solution or vapor phase with tunable morphologies and optoelectronic properties has greatly benefited the research for next-generation optoelectronic devices 10 12 . Although most of these device technologies, such as organic field-effect transistors (OFETs) 13 15 or light-emitting diodes 16 , have now become a conventional application avenue for molecular semiconductors, they hold huge promise also for unconventional applications such as surface-enhanced Raman spectroscopy (SERS). As we have recently disclosed in our pioneering studies 17 , 18 , the nanostructured organic films of π-electron-deficient fluorinated oligothiophene semiconductors DFH-4T 17 and DFP-4T 18 , fabricated via physical vapor deposition (PVD), enabled the Raman detection of organic analytes (e.g., methylene blue (MB) and rhodamine 6 G) without needing a metallic or an inorganic layer.…”
Section: Introductionmentioning
confidence: 99%
“…The poor electrical performances of Cu2O TFTs was attributed to a high density of defects at grain boundaries and at the semiconductor/dielectric interface, e.g., VOs and CuO secondary phase [21]. Several strategies are proposed to control these defects and to improve the performance and stability of Cu2O TFTs, including surface passivating [22,23], doping [24], using high-κ gate dielectrics (Al2O3, HfO2) [6]. For example, Chang and Nomura et al recently demonstrated the use of sulfur to reduce back-channel defect of p-type CuxO TFTs and achieved μsat of 1.38 cm 2 /Vs and on/off ratio of 4.1 × 10 6 [21].…”
Section: Cu2o Based Devicesmentioning
confidence: 99%